The growth share matrix as a planning tool: Caveats and practical problems - C. G. Robinson (South African Journal of Business Management, 1986)
Limitations exist on the naive application of the growth share and growth gain matrices as resource allocation techniques. This, the last in a series of three articles, points out some considerations essential for successful application of the Boston Consulting Group's approach to setting strategy. Thirteen caveats ranging from the breakdown of the implicit correlations between cash flows and market share and market growth rate through motivational and political problems must condition a competent analysis. Practical problems in implementing portfolio planning are highlighted.
Keywords: 650